Penggunaan Media Aksara Jawa Digital Dalam Pembelajaran Menulis Aksara Jawa - Ismiati; Darni; Resdianto Permata Raharjo; Anas Ahmadi (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
Javanese script is a cultural heritage of the Indonesian nation that has high historical, philosophical, and aesthetic value. However, in the context of education, student interest in learning Javanese script is still relatively low. Low student interest results in low Javanese script writing skills in students. Lack of Javanese script writing skills results in low student learning outcomes. This occurs because students have difficulty distinguishing the form of Javanese script that is almost similar, the lack of reading sources containing Javanese script, the lack of use of Javanese script in everyday life and the lack of learning media that is adaptive to the development of digital technology. These conditions require a solution, so in this study Rajagita Media becomes a solution to the problem of students' lack of skills in writing Javanese script and the low learning outcomes of writing Javanese script students of SMP Negeri 7 Madiun. This study aims to determine the process of implementing Rajagita media in learning to write Javanese script for grade IX students of SMP Negeri 7 Madiun which influences students' writing skills. This study used a quantitative approach with an experimental method, namely a Quasi-Experimental Design, applying a "post-test only control group design." The results of the study show that the process of implementing or using Rajagita media in the experimental class with the following steps: 1. Providing trigger questions in apperception, pre-test, introduction of Rajagita media and procedures for use, as well as group discussions and practice of writing Javanese script on various platforms independently by students, and discussions of various obstacles and challenges can have a significant impact on students' writing skills. These writing skills include neatness of writing, correct use of pairs and sandhangan, using scripts in words and sentences correctly. Students' writing skills have an impact on improving student learning outcomes. The increase in student learning outcomes is proven by the p-value = 0.000 <0.05, meaning the p-value is smaller than the significance level, so Ha is accepted, so the study shows that the use of Rajagita media has a positive effect on improving students' Javanese script writing skills. This is evidenced by the difference in the average post-test score in the experimental class using Rajagita media with a pre-test score of 68 and a post-test score of 68. 87, an increase of 19 points. The control class, which did not receive any treatment, had a pretest score of 67, increasing to 69, a 2-point increase. This difference in scores indicates that Rajagita media is effective as a learning medium in improving students' Javanese script writing skills. The conclusion of this study confirms that the process of using Rajagita media in learning has proven effective in developing students' Javanese script writing skills. The application of technology in education not only enriches learning methods but also contributes to the preservation of Javanese script and strengthening cultural literacy in the context of modern education.